Improving Teacher Performance and Education Quality through Madrasah Principal Leadership - Zaini, Mutmainnah; Barnoto, Barnoto; Ashari, Ashari (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The purpose of this research: 1). To determine the performance of teachers and the quality of education in MTs Nurul Hikam Kapongan. 2). To find out the leadership of madrasah principals’ performance and education quality. 3). To find out the supporting and habiting factors of madrasah leadership in improving teacher performance and the quality of education in MTs Nurul Hikam Kapongan Situbondo. In this study, a qualitative approach was used with a field observation study design. Data collection techniques with in-depth interviews, participant observation, and documented studies. The collected data is analyzed repeatedly. The credibility of the data is checked and matched between the results of the interview and the existing documents. The result of the study indicates that the decision-making is carried out by the head of the madrasah by considering the humanitarian side (high tolerance). Sometimes assisted by subordinates and sometimes the foundation participates in a structured, planned, programmed, and flexible process.